EMD carbon composite positive electrode material and preparation method thereof

By adding carbon material during the EMD grinding process and forming a carbon-coated carbon composite cathode material, the problem of uneven mixing between EMD and graphite is solved, and the conductivity of the battery and the utilization rate of EMD are improved.

CN119725431APending Publication Date: 2025-03-28WANBOLU MINING (CHINA) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411720605.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-28

Smart Images

  • Figure BDA0005157923780000061
    Figure BDA0005157923780000061
  • Figure BDA0005157923780000071
    Figure BDA0005157923780000071
Patent Text Reader

Abstract

The invention discloses an EMD carbon composite positive electrode material and a preparation method thereof, and particularly relates to the technical field of alkaline manganese battery materials. The method comprises the following steps: proportioning components of a carbon material and EMD, adding the carbon material in the process of grinding the EMD from an electrolytic sheet into EMD powder, and fully combining the EMD and the carbon material while grinding the EMD electrolytic sheet to be fine by controlling the EMD and the carbon material and the mixing ratio, so as to form the carbon-coated carbon composite positive electrode material. According to the invention, the carbon material is added in the process of grinding the EMD from fine particles into powder, and the grinding and mixing treatment is carried out, so that carbon coating is effectively formed, and the mixing effect is improved. The excellent carbon material is selected to be compounded with the EMD, so that the conductivity of the battery can be enhanced, and the internal resistance of the battery can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alkaline manganese battery materials, and in particular to an EMD carbon composite positive electrode material and a preparation method thereof. Background Art

[0002] Most of EMD will be used as positive electrode material for alkaline manganese batteries. In the process of making EMD into positive electrode material, because EMD itself is not conductive, it often needs to be mixed with graphite. However, the density of EMD is quite different from that of graphite. Therefore, in the conventional mechanical stirring and mixing process, EMD and graphite often cannot achieve the best mixing effect. Graphite often floats to the upper layer of the material instead of being evenly wrapped on the surface of EMD, which will cause uneven mixing of the whole material. This will lead to low utilization rate of EMD in the battery and poor conductivity of the electrode, thus affecting the discharge performance of the battery.

[0003] Under the existing technology, EMD and graphite are mixed after the EMD production process is completed and during the battery production process. Since EMD has completed the crushing process, in order to ensure that the optimal particle size is not destroyed, it is difficult to use a more powerful mixing technology during the mixing of graphite and EMD, so that graphite and EMD are only dispersed, and the dispersion effect is very limited.

[0004] Chinese patent CN112186149A, a manganese dioxide / graphite nanosheet composite zinc ion positive electrode material and its preparation method. The method comprises: using a mechanical ball milling preparation method to composite commercial manganese dioxide with graphite nanosheets, so that manganese dioxide can be dispersed on the surface of graphite nanosheets, to achieve the construction of a conductive network, thereby improving the efficiency of electron transmission, and the addition of graphite nanosheets significantly inhibits the volume change of manganese dioxide during the reaction process, thereby obtaining a high-performance and durable zinc ion battery positive electrode material. However, this patent requires the addition of abrasives during the ball milling process. As mentioned above, the density of EMD is quite different from that of graphite. Therefore, in the conventional mechanical stirring and mixing process, EMD and graphite often cannot achieve the best mixing effect. Graphite often floats to the upper layer of the material instead of being evenly wrapped on the surface of EMD, which causes uneven mixing of the entire material. And the method is to add manganese dioxide to the graphite nanosheets, and the obtained positive electrode material is that the manganese dioxide particles can be evenly dispersed on the surface of the graphite nanosheets, but the positive electrode material in which the manganese dioxide particles are evenly dispersed on the surface of the graphite nanosheets is not suitable for alkaline manganese batteries. Alkaline manganese batteries are more focused on the content of manganese dioxide, and the manganese dioxide content directly affects the capacity of alkaline manganese batteries. In addition, the manganese dioxide used in this patent is a product that has been sold after production, and it is a nano-level EMD product. The manganese dioxide used in this patent is a semi-finished product in the EMD production process, which is carried out by the grinding process in the production process, rather than using the EMD products sold. Summary of the invention

[0005] To this end, the present invention provides an EMD carbon composite positive electrode material and a preparation method thereof to solve the above-mentioned problems.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] According to one aspect of the present invention, a method for preparing an EMD carbon composite positive electrode material is provided, the method comprising: mixing the carbon material and the components of EMD, adding the carbon material in the process of grinding the EMD from an electrolyte sheet into EMD powder, and through the strong action of grinding, while the EMD electrolyte sheet is ground into finer pieces, fully combining with the carbon material to form a carbon-coated carbon composite positive electrode material.

[0008] In the present invention, carbon material is added during the process of grinding EMD from fine particles into powder, and grinding and mixing treatment is performed, thereby effectively forming carbon coating and improving the mixing effect.

[0009] The purpose of mixing carbon material with EMD is to enhance the conductivity of the battery and reduce the internal resistance of the battery. The carbon material and EMD need to be deeply coated, and the selection of different carbon materials is also particularly important. The present invention uses a carbon material with better conductivity and higher specific surface area to grind and mix with EMD to achieve good results.

[0010] Furthermore, the carbon material is selected from one or more of graphite, expanded graphite, acetylene black, carbon nanotubes, and graphene.

[0011] Furthermore, the carbon material is selected from a mixture of acetylene black and graphite.

[0012] Furthermore, the ratio of acetylene black to graphite is 1:1-50. As an example, 1:1 or 1:2 is preferred.

[0013] Furthermore, the carbon material is selected from a mixture of carbon nanotubes and graphite.

[0014] Furthermore, the ratio of the carbon nanotubes to the graphite is 1:(1-50); as an example, 1:2 is preferred.

[0015] Furthermore, the amount of carbon material added is 4%-10% of the mass of the EMD.

[0016] When the carbon material content is lower than 4%, the amount of carbon material added is too little and has no significant effect; when the carbon material content is higher than 10%, the amount of carbon material added is too much and affects the grinding effect, and the screening rate of EMD particles is reduced.

[0017] According to another aspect of the present invention, a carbon-coated positive electrode material is provided, and the positive electrode material is prepared by the above method.

[0018] The present invention has the following advantages:

[0019] In the present invention, carbon material is added during the process of grinding EMD from fine particles into powder, and grinding and mixing treatment is performed, thereby effectively forming carbon coating and improving the mixing effect.

[0020] The present invention selects excellent carbon materials to be compounded with EMD, which can not only enhance the conductivity of the battery, but also reduce the internal resistance of the battery.

[0021] The carbon-coated EMD positive electrode material prepared by the present invention not only does not need to add abrasives, but the positive electrode material obtained in this way is more suitable for the alkaline manganese battery industry, improves the utilization rate of EMD, and improves the performance of the battery. DETAILED DESCRIPTION

[0022] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1

[0024] This embodiment provides a method for preparing a carbon-coated positive electrode material:

[0025] 1.5 g of graphite was added during the grinding of 150 g of EMD electrolyte sheet, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0026] Example 2

[0027] This embodiment provides a method for preparing a carbon-coated positive electrode material:

[0028] 0.75 g of carbon nanotubes were added during the grinding of 150 g of EMD electrolyte sheet, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0029] Example 3

[0030] This embodiment provides a method for preparing a carbon-coated positive electrode material:

[0031] 3 g of graphite was added during the grinding process of 150 g of EMD electrolyte sheet, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0032] Example 4

[0033] This embodiment provides a method for preparing a carbon-coated positive electrode material:

[0034] 6 g of acetylene black was added during the grinding of 150 g of EMD electrolyte sheet, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0035] Example 5

[0036] This embodiment provides a method for preparing a carbon-coated positive electrode material:

[0037] During the grinding process of 150 g of EMD electrolyte sheet, 6 g of graphite and acetylene black (in a ratio of 1:1) were added, and after sufficient grinding and mixing, a carbon-coated carbon composite positive electrode material was obtained.

[0038] Example 6

[0039] This embodiment provides a method for preparing a carbon-coated positive electrode material:

[0040] During the grinding process of 150 g of EMD electrolyte sheet, 9 g of carbon nanotubes and graphite (in a ratio of 1:2) were added, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0041] Example 7

[0042] This embodiment provides a method for preparing a carbon-coated positive electrode material:

[0043] During the grinding process of 150 g of EMD electrolyte sheet, 9 g of carbon nanotubes and graphite (ratio of 1:50) were added, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0044] Example 8

[0045] This embodiment provides a method for preparing a carbon-coated positive electrode material:

[0046] During the grinding process of 150 g of EMD electrolyte sheet, 6 g of graphite and acetylene black (in a ratio of 8:1) were added, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0047] Example 9

[0048] This embodiment provides a method for preparing a carbon-coated positive electrode material:

[0049] During the grinding process of 150 g of EMD electrolyte sheet, 6 g of graphite and acetylene black (in a ratio of 50:1) were added, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0050] Comparative Example 1

[0051] This comparative example provides a method for preparing a carbon-coated positive electrode material:

[0052] During the grinding process of 150 g of EMD electrolyte sheet, no carbon material is added, and after sufficient grinding and mixing, a carbon-coated carbon composite positive electrode material is obtained.

[0053] Comparative Example 2

[0054] This comparative example provides a method for preparing a carbon-coated positive electrode material:

[0055] 0.6 g of graphite was added during the grinding of 150 g of EMD electrolyte sheet, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0056] Comparative Example 3

[0057] This comparative example provides a method for preparing a carbon-coated positive electrode material:

[0058] 16.5 g of graphite was added during the grinding of 150 g of EMD electrolyte sheet, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0059] Comparative Example 4

[0060] This comparative example provides a method for preparing a carbon-coated positive electrode material:

[0061] 1.5 g of graphite was added during the grinding process of 150 g of EMD electrolyte sheet, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0062] Comparative Example 5

[0063] This embodiment provides a method for preparing a carbon-coated positive electrode material:

[0064] During the grinding process of 150 g of EMD electrolyte sheet, 9 g of graphite and acetylene black (in a ratio of 2:1) were added, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0065] Comparative Example 6

[0066] This embodiment provides a method for preparing a carbon-coated positive electrode material:

[0067] 15 g of graphite was added during the grinding of 150 g of EMD electrolyte sheet, and the mixture was fully ground and mixed to obtain a carbon-coated carbon composite positive electrode material.

[0068] Comparative Example 7

[0069] Conventional EMD powder on the market is added with 10% graphite and directly mixed mechanically to obtain the positive electrode material.

[0070] Comparative Example 8

[0071] Electrolytic grade manganese dioxide particles with a diameter of 500 nm were mixed with graphite nanosheets in a mass ratio of 5:1, isopropanol was added as a grinding agent, and ball milling was performed at a rotation speed of 500 rpm for 3 hours to finally obtain a manganese dioxide / graphite nanosheet composite in which manganese dioxide particles were uniformly dispersed on the surface of the graphite nanosheets.

[0072] The carbon-coated carbon composite positive electrode materials obtained in Examples 1-9 and Comparative Examples 1-8 were sieved through a 60-mesh sieve and then neutralized with low stirring intensity to prevent graphite loss; after drying, they were mixed and granulated, and graphite was added to 6% of the total mass during granulation; after granulation by a granulator, they were made into positive electrode sheets using a tablet press and then made into button batteries for various tests. The results are shown in Table 1.

[0073] Table 1

[0074]

[0075]

[0076] As shown in Table 1, below 4%, the amount of carbon material added is too little and has no obvious effect; above 10%, the amount of carbon material added is too much and affects the grinding effect, and the screening rate of EMD particles is reduced;

[0077] Conductivity is shown by resistance. The stronger the conductivity, the lower the resistance. Under other conditions, the higher the utilization rate of EMD, the greater the capacity. The compaction density is generally related to the amount of graphite added. The more graphite is added, the lower the compaction density. The alkaline manganese battery industry requires products with higher compaction density.

[0078] Under the same battery manufacturing method, the EMD and carbon material mixture obtained by the grinding and mixing processing technology of the present invention is compared with the mixture of EMD products and graphite mechanically mixed. The capacity of the battery made by the new grinding and mixing technology is higher than that of the mechanically mixed samples. Compared with Comparative Examples 1 and 7, the present invention can improve the range by more than 4%. It can be seen from Examples 6-9 that the resistance of the present invention is significantly reduced and the capacity is improved.

[0079] The present invention prepares the carbon-coated EMD positive electrode material without adding an additional grinding agent, so that the obtained positive electrode material has a better mixing degree, thereby reducing the resistance and improving the utilization rate of EMD. The present invention limits the ratio of carbon material to EMD, and the final positive electrode material obtained is a carbon-coated EMD positive electrode material, which has lower resistance and higher compaction density than the manganese dioxide / graphite nanosheet composite in which manganese dioxide particles are uniformly dispersed on the surface of graphite nanosheets, and is more suitable for the alkaline manganese battery industry.

[0080] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A method for preparing an EMD carbon composite positive electrode material, characterized in that: The method comprises: mixing the carbon material and the EMD components according to the ratio, adding the carbon material in the process of grinding the EMD from the electrolyte sheet into the EMD powder, and controlling the mixing ratio of the EMD and the carbon material, so that the EMD electrolyte sheet is fully combined with the carbon material while being ground into fine pieces, thereby forming a carbon-coated carbon composite positive electrode material.

2. The method for preparing an EMD carbon composite positive electrode material according to claim 1, characterized in that: The carbon material is selected from one or more of graphite, expanded graphite, acetylene black, carbon nanotubes and graphene.

3. The method for preparing an EMD carbon composite positive electrode material according to claim 2, characterized in that: The carbon material is selected from a mixture of acetylene black and graphite.

4. The method for preparing an EMD carbon composite positive electrode material according to claim 3, characterized in that: The ratio of acetylene black to graphite is 1:(1-50).

5. The method for preparing an EMD carbon composite positive electrode material according to claim 4, characterized in that: The ratio of acetylene black to graphite is 1:

1.

6. The method for preparing an EMD carbon composite positive electrode material according to claim 2, characterized in that: The carbon material is selected from a mixture of carbon nanotubes and graphite.

7. The method for preparing an EMD carbon composite positive electrode material according to claim 2, characterized in that: The ratio of the carbon nanotube to the graphite is 1:(1-50).

8. The method for preparing an EMD carbon composite positive electrode material according to claim 7, characterized in that: The ratio of the carbon nanotubes to the graphite is 1:

2.

9. The method for preparing an EMD carbon composite positive electrode material according to claim 1, characterized in that: The added amount of the carbon material is 4%-10% of the mass of the EMD.

10. A carbon-coated positive electrode material, characterized in that: The positive electrode material is prepared by any method of claims 1-9.

Citation Information

Patent Citations

  • Manganese dioxide / graphite nanosheet composite zinc ion positive electrode material and preparation method thereof

    CN112186149A